Uplink NOMA Using Power Allocation for UAV-Aided CSMA/CA Networks - Kwon, Yohan; Baek, Hoki; Lim, Jaesung (IEEE Systems Journal, 2021)
One of the most attractive applications of unmanned aerial vehicles (UAVs) is deploying wireless communication systems. We consider a UAV-based low-Altitude platform (LAP) to deploy an aerial hotspot to provide Wi-Fi coverage without infrastructure and severe shadowing by urban or mountainous terrain. To address the performance degradation of carrier sense multiple access with collision avoidance (CSMA/CA) by increasing packet collisions with the number of clients, we exploit nonorthogonal multiple access (NOMA). To the best of authors' knowledge, there are no previous studies on uplink NOMA in CSMA/CA networks. In the considered system, owing to the distributed architecture and small channel difference of stations, conventional NOMA methods in cellular systems are not suitable. In this paper, we propose a power allocation scheme for uplink transmissions using predetermined power levels with a stochastic power selection to reduce the probability of packet collisions. A new medium access control procedure for uplink NOMA with CSMA/CA is also presented. The analytic results demonstrate that the proposed scheme achieves better saturation throughput and average packet delay than conventional CSMA/CA.
Keywords: Average packet delays; Carrier sense multiple access with collision avoidances; Distributed architecture; Mountainous terrain; Performance degradation; Saturation throughput; Up-link transmissions; Wireless communication system; Carrier sense multiple access; nonorthogonal multiple access (NOMA); power allocation; unmanned aerial vehicle-Aided wireless communication